FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERSONAL HYGIENE REMAJA PUTRI PADA SAAT MENSTRUASI DI SMP NEGERI 1 BANGKINANG - Putri Airiena Syakinah; Ade Dita Puteri; Syukrianti Syahda (LPPM Universitas Ekasakti, 2024)
During menstruation, young women's reproductive organs that are not kept clean are very susceptible to disease due to fungi, bacteria, parasites and viruses that are susceptible to entering the vaginal canal. So, young women during menstruation must pay attention to personal hygiene as best as possible to improve health from an early age and efforts to prevent disease. The aim of the research is to determine the factors related to the personal hygiene of young women during menstruation at SMP Negeri 1 Bangkinang in 2024. This type of research is quantitative analytical with a cross sectional research design, this research was carried out on 07-11 June 2024 at SMP Negeri 1 Bangkinang. The sample in this study was all female students in grades VII and VIII at SMP Negeri 1 Bangkinang totaling 90 female students according to the sample criteria. The sampling technique used was Total Sampling. The data collection tool in this research used a questionnaire. Data analysis in this study used univariate and bivariate analysis with the chi square test. The research results showed that there was a significant relationship between knowledge (p value 0.006), attitudes (p value 0.017), sources of information (p value 0.018) and personal hygiene during menstruation among young women at SMP Negeri 1 Bangkinang. It is hoped that young women will always pay attention to personal hygiene during menstruation in daily life to prevent or reduce itching in the feminine area, infections of the reproductive organs and urinary tract infections.